2020
DOI: 10.1108/heswbl-04-2019-0055
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of team communication skill among engineers: an empirical study

Abstract: PurposeThe purpose of the study is to understand the team communication skill among students with engineering background.Design/methodology/approachLabour market offers more employment to those who have better social skills than those who fair less on these skills. It is pertinent to integrate these skills among engineers. In the study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Some students relied on their confidence and paralinguistic communication skills such as voice modulation, facial expressions. They agreed that presentations helped them improve some fluency in English, they learnt to speak with clarity of thought and expression and acquired new wordsmost of these have been reported as problems of Indian engineers (Weider and Pratt, 1990;Clement and Murugavel, 2015;Mehta and Jha, 2020). The majority of the students admitted that they enjoyed working in a group, only a few felt they would have done better alone or as individual presenters.…”
Section: Findings Of the Studymentioning
confidence: 97%
See 1 more Smart Citation
“…Some students relied on their confidence and paralinguistic communication skills such as voice modulation, facial expressions. They agreed that presentations helped them improve some fluency in English, they learnt to speak with clarity of thought and expression and acquired new wordsmost of these have been reported as problems of Indian engineers (Weider and Pratt, 1990;Clement and Murugavel, 2015;Mehta and Jha, 2020). The majority of the students admitted that they enjoyed working in a group, only a few felt they would have done better alone or as individual presenters.…”
Section: Findings Of the Studymentioning
confidence: 97%
“…Their study successfully used presentation, technical writing and teamwork to teach engineering graphics. Similarly, presentations have been used to build communication skills in a team (Mehta and Jha, 2020). Another similar integrated approach to teaching language to engineers brought crossdisciplinary collaboration (Rice and Stetler, 2004) by making presentations a part of other disciplines.…”
Section: Presentation As a Tool To Explore Communication Skills: A Re...mentioning
confidence: 99%
“…Communication skills also allow an individual to identify and communicate the related information with a proper channel that facilitates the communication process. It is important to note that the development of social media globally has impacted communication skills as it allows an individual to gain access to the communication tools which enable the communication process to take place easily (Mehta & Jha, 2021). Creo et al (2020) stated that communication skills establish the proper tone and emotions among individuals so that communication can take place effectively.…”
Section: Communication Skillsmentioning
confidence: 99%
“…However, social media's role in enhancing education and information sharing still has pros and cons due to the lack of studies that validate the role of social media on information sharing in the education field. For instance, Abdur Rehman et al (2021) and Mehta and Jha (2021) applied a qualitative approach concluded during the COVID-19 pandemic, India faced limited quality interaction, motivation, class activities and interaction. Hence, we need a strategic approach (e.g.…”
Section: Introductionmentioning
confidence: 99%